Forensic DNA phenotyping Brazil : marcadores genéticos para fenótipos capilares - Flores, Klér Saraiva (2020)
The main goal in the forensic sciences researches is to find genetic markers for human identification that do not require a reference sample for comparison in criminal cases. Therefore, genetic markers that are capable of predicting externally visible characteristics that assist in identification, such as capillary phenotypes, are sought. The phenotypic characteristics associated with hair are dependent on the genetic background of the population, since it can vary according to ancestry and population biogeography. Because these characteristics are multigene, there is difficulty in isolating groups of single nucleotide polymorphisms (SNPs) that are associated with them. Thus, the aim of the present study was to suggest the custom correlation coefficient (CCC) as a statistical tool to be used in analyses of allelic associations with EVCs in the forensic area, using capillary phenotypes according to the content of eumelanin as an example. Ninety-nine SNPs located in genes associated with the synthesis of human melanin were genotyped from genes associated with the synthesis of human melanin from 358 volunteer participants for further allelic correlation analysis using the CCC tool. Allelic clusters according to the linkage disequilibrium were created. Then associations between clusters with the studied phenotype were tested using Fisher's exact test, where associations with p-value lower than 0.05 were considered significant. As a result, we obtained positive associations with phenotypes with high capillary eumelanin content, as well as with low content. From this, we could conclude that the CCC tool can be robust enough for analysis of allelic association with multigenic pigmentation characteristics, enabling its use in the routine of forensic investigations.